Elias Robot’s Effects on Students’ Willingness to Communicate in a Second Language from the Teacher Perspective : A Qualitative Study - Kantola, Juulia (My University, 2023)
Elias robot is a language learning application by Utelias Technologies Ltd that combines artificial intelligence, robotics, and speech recognition. Although called a robot, Elias robot is an application, not a robot. The application can be used through a social robot, Nao V5, Nao6, or Pepper robot, or from an electronic device, such as a phone or tablet. This study examines the possible effects of Elias robot on language learners' willingness to communicate from their teachers’ perspective, as well as the assumed reasons behind the possible effects. In addition, this study aims to assess the potential of Elias robot to increase students' L2 willingness in English from the teachers’ point of view. The data for the study were collected from five teachers with a semi-structured interview. The teachers have different educational backgrounds, they teach or different levels in Finland using different languages and have used Elias robot in their teaching. In the analysis of the qualitative data, a data-driven content analysis was utilized. Based on the analysis of the interviews, the teachers felt confident that Elias robot had had a positive impact on their students’ L2 willingness to communicate. Three themes were found as the assumed reasons behind the positive effect. The themes are increased motivation, emotional safety, and approachability. Regarding the third research question, the teachers thought Elias robot would succeed or has succeeded in raising students’ L2 willingness to communicate in English from their perspective. The study fills a gap by combining robot-assisted language learning and willingness to communicate. In the future, the same topic could be further studied from the learners’ point of view.
Keywords: willingness to communicate, robot-assisted language learning, L2 learning, spoken language